2007
DOI: 10.1158/0008-5472.can-07-0572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chromatin-Modifying Agents on CD34+ Cells from Patients with Idiopathic Myelofibrosis

Abstract: Idiopathic myelofibrosis (IM) is likely the consequence of both the acquisition of genetic mutations and epigenetic changes that silence critical genes that control cell proliferation, differentiation, and apoptosis. We have explored the effects of the sequential treatment with the DNA methyltransferase inhibitor, decitabine [5-aza-2 ¶-deoxycytidine (5azaD)], followed by the histone deacetylase inhibitor, trichostatin A (TSA), on the behavior of IM CD34 + cells. Unlike normal CD34

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…Low levels of CXCR4 expression were also reported in mobilized human CD34+ cells in PMF patients 59 . The biological consequences of reduced CXCR4 expression on these cells were identified by experiments showing that the CD34+CXCR4-cells from PMF patients had reduced capability to migrate in vitro toward a gradient of SDF-1 60 . The fact that reduced CXCR4 expression is implicated in abnormal cell trafficking in PMF is further suggested by the inverse correlation existing between CXCR4 expression and the number of circulating CD34 + cells that has been recently reported 59 .…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of CXCR4 expression were also reported in mobilized human CD34+ cells in PMF patients 59 . The biological consequences of reduced CXCR4 expression on these cells were identified by experiments showing that the CD34+CXCR4-cells from PMF patients had reduced capability to migrate in vitro toward a gradient of SDF-1 60 . The fact that reduced CXCR4 expression is implicated in abnormal cell trafficking in PMF is further suggested by the inverse correlation existing between CXCR4 expression and the number of circulating CD34 + cells that has been recently reported 59 .…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of 5azaD/SAHA treatment on PMF HPCs was similar to that previously reported with 5azaD/TSA treatment. 12 We further analyzed the JAK2V617F status of HPCs assayed from PMF CD34 ϩ cells treated with 5azaD/SAHA from 6 different patients (JAK2V617F granulocyte allelic burden of ranging from 35%-80%). CD34 ϩ cells were reisolated after treatment of cells from these same patients with cytokines alone or cytokines plus 5azaD/SAHA.…”
Section: Azad/saha Treatment Reduces the Percentage Of Malignant Pmfmentioning
confidence: 99%
“…11 In addition, we have reported that the sequential treatment of PMF CD34 ϩ cells with a DNA methyltransferase inhibitor, 5-aza-2Ј-deoxycytidine (5azaD), followed by an histone deacetylase (HDAC) inhibitor (HDACI), trichostatin A (TSA), resulted in an up-regulation of CXCR4 expression by PMF CD34 ϩ cells leading to correction of the abnormal cellular trafficking characteristic of PMF as well as a reduction of the burden of malignant hematopoietic progenitor cells (HPCs). 12,13 These preclinical studies illustrate the profound effects of chromatin-modifying agents (CMAs) on PMF HPCs and led us to further evaluate these strategies, this time using drugs that are currently approved for the treatment of other hematologic malignancies, and to determine whether they affect malignant stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…The reduced transcriptional activity of CXCR4 is caused by hypermethylation at specific CpG islands of the promoter, that reverted to normal state after short-term incubation with the demethylating agent 5-aza-deoxycitidine; furthermore, a significant reduction in the proportion of in vitro-generated JAK2 V617F mutated cells was observed after long-term incubation of CD34 þ cells with a combination of 5-azacitidine and an histone deacetylase (HDAC) inhibitor. 75 These treatments also resulted in the correction of the abnormal in vitro migratory characteristics of CD34 þ cells 76 and in their seeding in the bone marrow of NOD/SCID mice. 77 However, a global methylome profile of MPD cells is not yet available, and the significance of these observations still needs to be confirmed.…”
Section: Novel Mechanisms In Mpdsmentioning
confidence: 99%